Comparative Analysis of Corona Discharge Characteristics in High Voltage AC and DC Transmission Lines : Comparative Analysis of Corona Discharge Characteristics in High Voltage AC and DC Transmission Lines - Lesuanu Dumkhana (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
The increasing demand for reliable long-distance electricity transmission has elevated the importance of understanding corona discharge phenomena in high-voltage AC (HVAC) and DC (HVDC) transmission lines. Corona discharge, caused by local electric fields exceeding air breakdown strength, contributes to power losses, audible noise, and electromagnetic interference, which collectively reduce system efficiency and operational reliability. This study investigates the behavior of corona under varying environmental and conductor conditions, focusing on pressure, humidity, and surface roughness, which are known to influence onset voltage, power loss, and noise emissions. A combination of empirical modeling and regression-based analysis was employed, incorporating effective breakdown field estimations, geometric voltage scaling, AC/DC mode corrections, and power-law relationships for corona current and power loss. Experimental and simulation results demonstrate that the breakdown field is maximized at 3.0 MV/m under high pressure (105 kPa) and low humidity (10%), while decreasing to 1.9 MV/m at 80 kPa and 95% humidity. Corona onset voltage decreases with surface roughness, with AC voltage dropping from 72.0 kV to 56.4 kV and DC voltage from 78.0 kV to 61.2 kV over roughness ranges of 0.5–50 ?m. Power losses scale with excess voltage, with AC losses following and DC losses . Audible noise increases from 24 dB(A) to 71 dB(A) as power loss rises, with surface roughness and humidity amplifying the effect. Sensitivity analysis identifies surface roughness and humidity as dominant factors, while AC lines exhibit 14% higher power losses and 13% higher noise levels than DC lines. The findings provide quantitative insights for transmission line design and operational policies, emphasizing the need for surface maintenance and humidity mitigation strategies to enhance efficiency, reduce energy losses, and comply with environmental noise standards.